Posterior Reversible Encephalopathy Syndrome and Reversible Cerebral Vasoconstriction Syndrome: Clinical and Radiological Considerations - Pilato, Fabio; Distefano, Marisa; Calandrelli, Rosalinda (Frontiers in Neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) and reversible cerebral vasoconstriction syndrome (RCVS) are relatively uncommon neurological disorders but their detection has been increasing mainly due to clinical awareness and spreading of magnetic resonance imaging (MRI) in the diagnostic pathway. Because these syndromes share some common characteristics and they may be present in the same patient occasionally, even if they have specific neurological and neuroradiological features, misdiagnosis may occur. PRES is characterized by varied neurological symptoms including headache, impaired visual acuity or visual field deficits, confusion, disorders of consciousness, seizures and motor neurological deficits with specific neuroradiological pattern and ischemic or hemorrhagic lesions in the brain may occur. Reversible cerebral vasoconstriction syndrome (RCVS) is a group of syndromes characterized by reversible segmental constriction of cerebral arteries, typically associated with severe headaches and often complicated by ischemic or hemorrhagic stroke. Pathophysiological basis of PRES and RCVS are still debated even if they share some risk factors and clinical course. Clinical course usually is self-limiting, but prognosis is unpredictable varying from complete recovery to death due to complication of ischemic stroke or intracranial hemorrhage and factors related to prognosis are still debated. MRI may be helpful in diagnostic pathway and a possible prognostic role has also been suggested. This review will serve to summarize the specific neurological, neuroradiological characteristics and controversies underlying both syndromes in the diagnostic pathway and their possible relationship with prognosis.